Maternal Attitude in the Handling of Diarrhea in Infant - Desta Ayu Cahya Rosyida; Nina Hidayatunnikmah (Universitas Muhammadiyah Yogyakarta, 2020)
Diarrhea According to epidemiological theory is influenced by 3 factors, namely host, Agent and environment. The host is a landlady or as it is occupied for instance age, nutritional status. Diarrhoea disease in infants whose nutritional status is bad is more difficult to heal because of the damaged intestinal mucosa in the process of a longer revitalization. From the Government Health Service data of Jember District, in May 2008 the number of Diarrhea suffered reaches 4,601. In January 2008, the number of diarrhea sufferers reached 5,202 people, February 5,361, March 4,754, and April 4,755 sufferers. Of these, people less than 5 years old reach 70 percent. The purpose of this research to Analyzed attitude of mother in the treatment of diarrhea in an infant in the health centre of Arjasa District Regency of Jember. The research method used cross-sectional study. The population of this study was toddlers with diarrhea of 58 children. Non-probability sampling technique with consecutive sampling types (which meet the inclusion and exclusion criteria).The information regarding maternal attitude was obtained by questionnaire. Statistic test used descriptive analysis. Analysis results indicate that mothers with positive attitude find 26-35 years old, the last education of Junior and Senior High School, a job as a housewife. Based on 35 samples, it shows that mothers with a positive attitude are 27 and mothers with negative attitude is 8. The results of this study are maternal have a positive attitude to give ORS on handling diarrhea in an Infant.